2022
DOI: 10.18267/j.pep.816
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Household Mortgage Debt: the case of the Czech Republic

Abstract: This paper deals with Czech household mortgage debt and its determinants in the period 1Q2005-2Q2021. Our analysis focuses on the variables determining the level of mortgage debt from both short-and long-term perspectives. Our contribution is two-fold. Firstly, we examine the relationship between the selected variables within a cross-correlation analysis. The results confirm the positive dependency of household mortgage debt and real GDP, real gross average income and the level of house prices. By contrast, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The reason is that design optimization of RC corresponds to pre-processing research of rebars optimization, while CWM of rebars covered in this study corresponds to post-processing research. As a result of reviewing some of the literature related to design optimizations of rebars, it was confirmed that they are related to design optimization of RC components such as slab [50][51][52][53][54][55][56][57], beam [58][59][60][61], column [62][63][64][65], foundation [64], and wall [66][67][68], and design optimization of RC frames such as bridges [69][70][71] and building [72]. In addition, many studies related to design optimization have been well-organized in the review article [37].…”
Section: Methodsmentioning
confidence: 97%
“…The reason is that design optimization of RC corresponds to pre-processing research of rebars optimization, while CWM of rebars covered in this study corresponds to post-processing research. As a result of reviewing some of the literature related to design optimizations of rebars, it was confirmed that they are related to design optimization of RC components such as slab [50][51][52][53][54][55][56][57], beam [58][59][60][61], column [62][63][64][65], foundation [64], and wall [66][67][68], and design optimization of RC frames such as bridges [69][70][71] and building [72]. In addition, many studies related to design optimization have been well-organized in the review article [37].…”
Section: Methodsmentioning
confidence: 97%
“…This method is also described by various authors, e.g., Kubišová in the field of operational research, as well as authors dealing with management and decision-making processes in management, such as Fiala and the collective, Žáček, Fotr J. and Dědina J. in the book Managerial Decisions from 1993 [24]. Specifically, Fiala [25] and the collective stated the theoretical basis of multi-criteria decision making: "multi-criteria decision-making tasks are those decision-making tasks whose consequences of the decision are assessed according to several criteria. If the set of admissible variants is finite, then we speak of the task of multi-criteria evaluation of variants.…”
Section: Methodsmentioning
confidence: 99%
“…If the set of admissible variants is finite, then we speak of the task of multi-criteria evaluation of variants. However, if the set of admissible variants is defined by a set of conditions that the decision alternatives must meet, it is a task of multi-criteria programming" [25] (p. 16).…”
Section: Methodsmentioning
confidence: 99%